Effects of melatonin and bacterial bio-stimulants on calendula officinalis under salinity stress - Omniea M. Allam; Awaad M. Kandeel; Sohair E. Hassan; Ahmed N. Abdelhamid (Journal of the Saudi Society of Agricultural Sciences)
Abstract Melatonin can mitigate the adverse effects of salt stress in plants, but the combined effects of it and bacterial bio-stimulants on enhancing plant resilience to salinity remain poorly understood. To fill in such a knowledge gap, we investigated the interaction between melatonin and bacterial bio-stimulants on the growth, productivity, and physiological characteristics of Calendula officinalis seedlings under salt stress. Using a pot-sand culture method, we tested various concentrations of exogenous melatonin (distilled water, 50, 100 µM) combined with a bacterial mixture (5 ml/pot at 108 CFU/ml) of Azotobacter chroococcum, Bacillus megaterium, and Pseudomonas fluorescens. The seedlings were subjected to different saline irrigation levels with NaCl (tap water, 42.8, 85.6, and 128.3 mM) over two growing seasons in 2023 and 2024. The experiment was designed as a factorial study using a randomized complete block design with three replicates. NaCl concentrations of 85.6 mM and 128.3 mM negatively affected seedling growth and yield. Foliar application of 100 µM melatonin combined with bacterial inoculation significantly enhanced leaf area and shoot dry weight. Inflorescence parameters improved notably, with increases in total carotenoids and flavonoids in petals. Total chlorophyll content, mineral percentages (N, P, K), and proline increased significantly, while sodium and chloride levels decreased. The activities of polyphenol oxidase and peroxidase increased significantly and also improved relative water content and reduced electrolyte leakage. Our findings suggest that the combination of exogenous melatonin and bacterial inoculation can effectively mitigate the adverse effects of salt stress on Calendula seedlings.